2022
DOI: 10.1021/acsami.1c21948
|View full text |Cite
|
Sign up to set email alerts
|

Surface Passivation of MAPbBr3 Perovskite Single Crystals to Suppress Ion Migration and Enhance Photoelectronic Performance

Abstract: Recently, organometal halide perovskites (OHPs) have achieved significant advancement in photovoltaics, lightemitting diodes, X-ray detectors, and transistors. However, commercialization and practical applications were hindered by the notorious ion migration issue of OHPs. Here, we report a simple solvent-based surface passivation strategy with organic halide salts (methylammonium bromide (MABr) and phenylethylammonium bromide (PEABr)) to suppress the ion migration of MAPbBr 3 single crystals. The surface pass… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

3
52
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 59 publications
(55 citation statements)
references
References 56 publications
3
52
0
Order By: Relevance
“…The unwashed NC films exhibit a broad diffraction peak at 19.5°, and this peak goes away with the washing of the NCs. It was earlier attributed to the excess passivating ligands. We found that the plasma treatment does not cause any major structural change or generate impurities like PbBr 2 , commonly found as a byproduct of degradation. , However, if we carefully observe the normalized diffraction pattern, the relative intensity ratio of the (220)/(112) peak increases. We deconvoluted the XRD patterns to quantify the relative intensity ratio of the (220)/(112) peak as shown in Figure S4a-d.…”
Section: Resultsmentioning
confidence: 77%
See 1 more Smart Citation
“…The unwashed NC films exhibit a broad diffraction peak at 19.5°, and this peak goes away with the washing of the NCs. It was earlier attributed to the excess passivating ligands. We found that the plasma treatment does not cause any major structural change or generate impurities like PbBr 2 , commonly found as a byproduct of degradation. , However, if we carefully observe the normalized diffraction pattern, the relative intensity ratio of the (220)/(112) peak increases. We deconvoluted the XRD patterns to quantify the relative intensity ratio of the (220)/(112) peak as shown in Figure S4a-d.…”
Section: Resultsmentioning
confidence: 77%
“…The photoluminesce properties of nanocrystals are strongly affected by the surface defects. To probe if plasma treatment causes any changes in the surface defects of the CsPbBr 3 NCs, we performed time-correlated single-photon counting (TCSPC) measurements on the thin films without and with plasma treatment (Figure f). The biexponential decay fit (Figure S5) of TCSPC spectra suggested two different decay paths in all the CsPbBr 3 NC films.…”
Section: Resultsmentioning
confidence: 99%
“…In view of this, the exact nature of traps and their effect on the optoelectronic properties are under active investigation. Many efforts have been devoted to passivate the defects to increase the stability and performance of the halide perovskite SCs. To this end, one approach is to treat the crystals with various Lewis acid- or base-based ligands after synthesis ,, or to control the growth of SCs using additives. , Duim et al investigated the mechanism of surface passivation of methylammonium lead tribromide (MAPbBr 3 ) SCs using benzylamine, and it was reported that exposure to benzylamine results in the formation of two-dimensional (2D) (BA) 2 PbBr 4 on the surface of a three-dimensional (3D) perovskite by replacing the methylammonium cations . They studied the mechanism of surface passivation and stabilization of the 2D perovskite using in situ imaging.…”
Section: Introductionmentioning
confidence: 99%
“…22 2-Phenylethanamine bromide (PEABr) can serve as a capping ligand to hamper ion migration and passivate perovskite QDs. [23][24][25] Hence, we selected it as an additive to further protect CsPbBr 3 QDs. PEABr has better hydrophobicity due to its longer alkyl chain than BA, and hence it could compensate for the stripped BA in photocatalysis, and Br − can fill in the bromide vacancy defects on the QD surface.…”
Section: Introductionmentioning
confidence: 99%